Socializing the classroom social networks and online learning - Barnes, Susan B.; ebrary, Inc. (Lanham : Lexington Books, 2012)
"Socializing the Classroom: Social Networks and Online Learning, by Susan B. Barnes, examines how social media can be used in education through two research grants and real-world applications. Barnes analyzes social media including Facebook, Courseware, and Second Life, while providing a theoretical foundation for examining social software. A new generation of students is surrounded by digital technologies, leading scholars and teachers to consider virtual worlds to engage students"-- Provided by publisher.
Machine generated contents note: Introduction -- Chapter 1: What are Social Media? -- Chapter 2: Self Identity and Awareness -- Chapter 3: Space Versus Place -- Chapter 4: Structure of Networking Communities -- Chapter 5: Awareness and Notification -- Chapter 6: Second Life and Social Presence -- Chapter 7: Ethical Issues in Virtual Worlds -- Chapter 8: Social Norms -- Chapter 9: Trust Online -- Chapter 10: Remix Culture -- Chapter 11: Social Capital: The Goal of Social Networking -- Conclusion.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Internet in education; Social media; Education -- Effect of technological innovations on; Electronic books